Development of Early Warning Systems and Structural-Non-Structural Strategies for Flood Management in Urban Industrial Area - Ashruri; Tri Budi Wibowo; Ismail, M Rizky; Ahmad Zakaria; Muhammad Haviz (WISE Pendidikan Indonesia, 2025)
This study aims to develop a holistic flood mitigation framework for the Jababeka Industrial Estate, a region increasingly affected by flooding due to accelerated land-use changes, diminished infiltration capacity, and insufficient drainage systems. The research integrates both structural and non-structural components, including the conceptualization of a real-time early warning system tailored for industrial urban environments. The methodology involved a detailed hydrological evaluation based on a decade of rainfall records collected from three meteorological stations. These data underwent consistency assessments using RAPS, trend analysis, and outlier detection, followed by the calculation of regional average rainfall through the Thiessen polygon method. Statistical distributions were applied to generate design rainfall values for return periods of 2 to 100 years, and flood discharges were estimated using four synthetic unit hydrograph (SUH) models: Snyder, Nakayasu, GAMA I, and ITB. Simulation of flood scenarios was conducted with the HEC-HMS platform, and field assessments were used to identify critical infrastructure deficiencies. The analysis revealed high-risk areas requiring structural upgrades such as river channel improvements, the addition of retention basins, and enhanced pumping systems. Additionally, the study proposes a sensor-integrated early warning mechanism capable of transmitting automatic alerts to stakeholders. The integrated strategy demonstrated here offers a scalable and transferable model for climate-resilient flood management, particularly relevant for rapidly urbanizing industrial zones facing intensifying hydrometeorological threats due to climate change and unregulated development.